Zhong guo fo jiao shi jing = Buddhist stone sutras in China / Shan xi Sheng Di 1 juan Jin chuan wan shi ku dong bi = Jinchuanwan Cave, East Wall / edited by Zhao Rong and Lothar Ledderose / ben juan zhu bian: Zhao Rong, Lei De hou - Ledderose, Lothar; Zhao, Rong (Zhong guo fo jiao shi jing = Buddhist stone sutras in China, 2020)
The first volume of the three-volume series on Buddhist stone sutras in Shaanxi presents the engravings on the east wall of the Jinchuanwan cave. With almost 160,000 characters, this cave is the one with the largest amount of texts in China. From 2007 to 2012 the Shaanxi Provincial Institute of Cultural Relics Protection restored the cave in cooperation with the Bayerisches Landesamt für Denkmalpflege. The cave was built in the 660s by followers of the Three Levels School. The school was suppressed soon thereafter and its texts fell into oblivion in China. Texts by the school?s patriarch Xinxing (540?594) are only preserved by chance, as it were, in the far west in the caves at Dunhuang and in Japan. 0Two major texts have now been added to this corpus in Jinchuanwan cave, which were completely unknown so far; they were only discovered in the 1990s. In total, the cave contains four of Xinxing?s texts. His three texts on the East wall are here presented for the first time, and the two major ones are translated into English and analyzed in a separate essay. In addition to the texts themselves, the restoration of the Jinchuanwan cave is presented as well as the history of the Three Levels School with its major figures, teachings and material remains. All texts are transcribed and fully documented with photographs and rubbings. This research has been conducted under the auspices of the Heidelberger Akademie der Wissenschaften by an international team led by Lothar Ledderose and supported by the cultural authorities in China. The volumes, bilingual in Chinese and English, address a wide audience